2002
DOI: 10.1056/nejmoa012385
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Prophylaxis against Venous Thromboembolism with Enoxaparin after Surgery for Cancer

Abstract: Enoxaparin prophylaxis for four weeks after surgery for abdominal or pelvic cancer is safe and significantly reduces the incidence of venographically demonstrated thrombosis, as compared with enoxaparin prophylaxis for one week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
484
4
22

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 963 publications
(524 citation statements)
references
References 18 publications
14
484
4
22
Order By: Relevance
“…6000 u of enoxaparin for BMI [30 kg/m 2 , 8000 u for BMI [40 kg/m 2 , 10,000 u for BMI [50 kg/m 2 ) has been shown to be safe without increased risk of bleeding [182][183][184]. Finally, many studies indicate prolonged risk of thrombotic events, not least due to unpredictable food intake in some patients, encouraging recommendation of 3-4 weeks treatment [185,186]. There are no data suggesting that the use of fondaparinux or other new oral anticoagulants should be recommended.…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…6000 u of enoxaparin for BMI [30 kg/m 2 , 8000 u for BMI [40 kg/m 2 , 10,000 u for BMI [50 kg/m 2 ) has been shown to be safe without increased risk of bleeding [182][183][184]. Finally, many studies indicate prolonged risk of thrombotic events, not least due to unpredictable food intake in some patients, encouraging recommendation of 3-4 weeks treatment [185,186]. There are no data suggesting that the use of fondaparinux or other new oral anticoagulants should be recommended.…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…The ENOXACAN II study 12 found a relative risk reduction of 60% (p = 0.02); however, the benefit of extended treatment was predominantly in the reduction of asymptomatic distal DVT, which is of questionable significance. Another major limitation was that only about half of the patients recruited for the study were accounted for in the outcome assessment.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated that incidence of VTE after discharge would be about 1%. 8,12,14 In order to be 95% confident that the true incidence is within ± 1%, 381 patients needed to be included in the sample. Therefore our study had more than enough power to reach its primary objective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations